(3cJGH LdGd Ydi GdJgPjHs - (3LdGd GdOjf eMeO Hf CSYO GdUOjbi GdOhGfis; (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s
(3ChdgG (B:s
(3JgPjH GdefWb hGdcdGe hHYO agPg YLGdI hZdGdI QGHMI JQhi Zdjd WGdHi UfGYI GdejRGf s
(3BNQgG (B:s
(3ai GdHYV dGJfYcS ef ZjQgG PcQ GdehLHGJ GdcdjI GdTQWjI JfYcS HYcS GdfbjV s
(3GdfSNI HgG MhGTs
(3Ydi GdeNWhW MGTjI ejQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B219 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B228 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B430s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B516s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs